Implementation of Land Acquisition Policy in The Perspective of Social Justice For Indigenous Peoples in Sorong City - Ludia Baransano; Karmanis Karmanis; Tri Lestari Hadiati (International Forum of Researchers and Lecturers, 2026)
This research aims to analyze the implementation of land acquisition policies in Sorong City from the perspective of social justice for indigenous peoples, and to evaluate the extent to which customary rights are accommodated in the development process. The research method is a mixed-methods study with an embedded design. The qualitative approach was the primary instrument, using in-depth interviews with five key speakers, including land authorities and representatives of the Malaloi Indigenous Peoples Institution (LMA). Quantitative approaches are used only in correlation analysis to reinforce qualitative findings. The study's results show a